Reparations for Cultural Loss to Survivors of Indian Residential Schools - Mallam, Andrew J (University of Ottawa (Canada), 2010)
This paper is an investigation into appropriate forms of reparation to compensate survivors and descendants of survivors of Indian Residential Schools for loss of culture. Indian Residential Schools perpetrated serious individual abuses upon pupils; however, Aboriginal peoples as a group also sustained a serious harm -- an injury to their culture. Whereas tort law and alternative dispute resolution mechanisms have provided redress for individual losses, a group-oriented reparations solution is required to compensate for cultural loss. This paper will set out the historical record of the school policy, and investigate the nature of the loss, i.e. culture, and its intergenerational relationships. The methods by which common law courts have dealt with contemporary cultural loss claims will be outlined, as well as the reparations scheme that has been implemented by the Canadian government. After analyzing the legal and non-legal responses to claims for loss of culture, a legislative solution will be offered that aims to protect and promote Aboriginal culture as it stands in Canada today.
Keywords: Law.; Native American Studies.